Developing Speaking Competence for Community-Based Tourism: A Case Study in Klaten Regency, Indonesia - Sri Wahyuni Samaratul Zanah (Jurnal Bahasa, Sastra, dan Studi Amerika, 2025)
Speaking skills play a vital role in the tourism industry, particularly in community-based destinations where local residents interact directly with visitors. This study explores the development of speaking competence among tourism actors in a rural tourism village in Klaten Regency, Central Java. It aims to identify language needs, analyze challenges in English oral communication, and recommend pedagogical strategies for English for Tourism (EfT) instruction. The findings, derived from observation, interviews, and document analysis, indicate that limited vocabulary, lack of confidence, and insufficient exposure to authentic communicative practice hinder local guides and hosts in delivering quality tourist experiences. The study highlights the effectiveness of task-based learning, role-play, and digital storytelling as contextually relevant approaches to enhance speaking competence in tourism education and community training programs.